Identifying SVARs from sparse narrative instruments: Dynamic effects of U.S. macroprudential policies - Katarzyna Budnik; Gerhard Rünstler (European Central Bank (ECB), 2020)
We study the identification of policy shocks in Bayesian proxy VARs for the case that the instrument consists of sparse qualitative observations indicating the signs of certain shocks. We propose two identification schemes, i.e. linear discriminant analysis and a non-parametric sign concordance criterion. Monte Carlo simulations suggest that these provide more accurate confidence bounds than standard proxy VARs and are more efficient than local projections. Our application to U.S. macroprudential policies finds persistent effects of capital re- quirements and mortgage underwriting standards on credit volumes and house prices together with moderate effects on GDP and in ation.
Keywords: C32; E44; G38; 330; Bayesian Proxy VAR; Discriminant Analysis; Sign Concordance; Capital Requirements; Mortgage Underwriting Standards